Practical guide to exercise physiology the science of exercise training and performance nutrition - Murray, Robert 1949-; Kenney, W. Larry (Human Kinetics, Inc., 2021)
"Practical Guide to Exercise Physiology: The Science of Exercise Training and Performance Nutrition, 2nd Edition takes an application-based approach in describing intricate physiological processes. The text is complemented by medical and infographic-like artwork to illustrate complex systems. These systems are then applied to real-world practice and training principles to help clients achieve the desired results. Pedagogical aids support students, and professionals will be better equipped to design exercise programs for various populations and to explain to clients the principles that will help them achieve their goals"